The effects of different PMSG doses on estrus behavior and pregnancy rate in Angora goats. (27th July 2018) - Tirpan, M. B.; Tekin, K.; Cil, B.; Alemdar, H.; Inanc, M. E.; Olgac, K. T.; Stelletta, C.; Daskin, A.
Abstract : Artificial insemination protocols depend on efficient behavioral estrus detection and insemination time in Angora goat. Therefore, we aim to determine the accuracy of an estrus scoring system in Angora goats with different PMSG doses during the breeding season. Does ( n : 260) were randomly divided into three groups: group-1 ( n : 93), group-2 ( n : 85) and group-3 ( n : 82). All animals received an intravaginal sponge on day 0 for 11 days, and on the day of sponge insertion 150 μg prostaglandin F2Α was administered. Pregnant mare's serum gonadotropin was injected 300, 400 and 500 IU intramuscularly 24 h before sponge removal to groups 1, 2 and 3, respectively. Estrus signs were detected with a teaser buck, 24 h after sponge removal according to a visual scoring system. Artificial insemination was performed with 0.25 ml fresh diluted semen at 43 to 45 h after sponge removal. Differences were observed within PMSG groups in terms of standing, tail wagging, courtship behavior, vaginal discharge and vaginal hyperemia ( P <0.001). Nevertheless, the most accurate indicators of estrus that result in pregnancy were tail wagging and courtship behavior followed by standing estrus ( P <0.05). According to the results obtained, 300 IU PMSG dose is sufficient, both to inseminate at a fixed time (43 to 45 h after sponge removal) and to record the estrus behavior by teaser male 24 h after sponge removal. Higher PMSG doses (400 to 500 IU) altered the timing of ovulation; specifically, 500 IU dose shortened the duration of estrus behaviors. In conclusion, even though the different doses of PMSG displayed similar effects on estrus synchronization and pregnancy rates, we concluded that tail wagging, courtship behavior and standing heat are the most reliable estrus signs for artificial insemination in Angora goat.